Implementation of Self-Monitoring Technique through Reading Comprehension in Critical Reading Class - kevin Danis wara (Retain: Journal of Research in English Language Teaching, 2024)
Abstrak Studi penelitian ini menyelidiki implementasi teknik self-monitoring dalam meningkatkan pemahaman membaca di kalangan siswa sekolah menengah atas. Studi ini bertujuan untuk mengeksplorasi bagaimana siswa menggunakan strategi self-monitoring, efektivitas strategi tersebut dalam meningkatkan pemahaman membaca, dan tanggapan siswa terhadap self-monitoring. Penelitian dilakukan di kelas sepuluh untuk mengatasi kebiasaan membaca siswa dan kurangnya minat dalam membaca. Metode pengumpulan data meliputi observasi teknik membaca siswa, memberikan cerita pendek untuk berpikir kritis dan self-monitoring, dan menyelenggarakan kuesioner untuk mengevaluasi kemajuan selama implementasi self-monitoring. Studi ini menekankan pentingnya pembelajaran self-regulated dan keterampilan metakognitif dalam meningkatkan kemampuan membaca. Temuan mengungkapkan bahwa siswa aktif terlibat dalam self-monitoring dengan menggunakan simbol, self-translation, troubleshooting, dan mencari bantuan untuk meningkatkan pemahaman. Siswa melihat self-monitoring secara positif, mengakui manfaatnya dalam meningkatkan kesadaran, pemberdayaan, dan pemahaman. Penelitian ini berkontribusi pada pemahaman dampak self-monitoring pada keterampilan membaca siswa dan menyoroti pentingnya pembelajaran self-regulated dalam pengaturan pendidikan. Kata Kunci: Self-monitoring, Pemahaman membaca, Siswa sekolah menengah Abstract This research study investigates the implementation of self-monitoring techniques in improving reading comprehension among senior high school students. The study aims to explore how students utilize self-monitoring strategies, the effectiveness of these strategies in enhancing reading comprehension, and students' responses towards self-monitoring. The research is conducted in a tenth-grade class to address students' reading habits and lack of interest in reading. Data collection methods include observation of students' reading techniques, providing short stories for critical thinking and self-monitoring, and administering questionnaires to evaluate progress during self-monitoring implementation. The study emphasizes the importance of self-regulated learning and metacognitive skills in improving reading abilities. Findings reveal that students actively engage in self-monitoring by using symbols, self-translation, troubleshooting, and seeking help to enhance comprehension. Students perceive self-monitoring positively, acknowledging its benefits in increasing awareness, empowerment, and comprehension. The research contributes to understanding the impact of self-monitoring on students' reading skills and highlights the significance of self-regulated learning in educational settings. Keywords: Self-monitoring, Reading comprehension, High school students